Front Cover. Issue 1 (4th January 2019) - Sukriti, Sukriti; Choudhary, Manish Chandra; Maras, Jaswinder Singh; Sharma, Sachin; Thangariyal, Swati; Singh, Avishek; Das, Sukanto; Islam, Mojahidul; Sharma, Shvetank; Trehanpati, Nirupama; Gupta, Ekta; Sarin, Shiv Kumar
Abstract : The cover image is based on the Short Communication Extracellular vesicles from hepatitis B patients serve as reservoir of hepatitis B virus DNA by Sukriti Sukriti et al., https://doi.org/10.1111/jvh.12995 .